Making Mobile Feedback Programs Work : Lessons from Designing an ICT Tool with Local Communities - Lee, Panthea; Schaefer, Merrick (World Bank, Washington, DC, 2014)
Does providing a free text messaging (SMS) reporting tool, which facilitates communication between farmers and the state-level Project Implementation Unit (PIU) overseeing the Fadama III Project, improve the quality of service of the program? This note highlights initial outcomes from a pre-pilot exercise conducted in 2013 with two program objectives: 1) to explore whether working with local Community-Based Organizations (CBO) to train farmers to use and to promote the tool was an effective means to get and maintain user adoption; and 2) to examine whether the ICT-generated information and system helped the PIU better manage the project. Two main conclusions can be drawn from this pre-pilot. Firstly, it was found that CBO engagement led to significantly larger uptake and use of the system. Secondly, the State PIU only minimally used the reports that were being sent by farmers, despite institutional excitement about the system and a strong mandate from management to use the reports. The findings presented here are based on the deployment of MyVoice, a prototype SMS tool, in six communities in the Federal Capitol Territory of Nigeria. The tool was rolled out over a two-week period through training sessions in the community. The tool was then left operational for an additional four weeks for the communities and government to utilize it. The data informing this note was from all six weeks. Despite the fact that the prototype had significant technical and usability limitations, which were well-understood by the implementing team, its deployment allowed the team to test and learn about the social adoption and use of the tool, as well as to refine the program, training and final software for a more formal pilot and launch. This responsive and adaptive approach helped the team build a more locally relevant and useful system.